Evaluation of e-star: An enhanced science textbook using augmented reality among lower secondary school student - Gopalan, Valarmathie; Zulkifli, Abdul Nasir; Faisal Mohamed, Nur Fadziana; Alwi, Asmidah; Che Mat, Ruzinoor; Abu Bakar, Juliana Aida; Saidin, Aeni Zuhana (Penerbit UTM Press, 2015)
As a developing country, Malaysia needs to produce adequate human resource in science and technology related fields.This is important especially towards making Malaysia a developed nation by 2020. Unfortunately, there is a downward trend in the number of students pursuing the science stream at the secondary education level.Lack of motivation has been identified as one of the cause of this phenomenon.This paper introduces an enhanced science textbook using Augmented Reality (e-STAR) application that facilitates students in science learning.The e-STAR is intended to motivate the students to be more interested in science. This paper also discusses on the evaluation of the e-STAR among a sample of form two secondary school students. Quantitative data was collected using questionnaires for evaluating the following dimensions: motivation, ease of use, engaging, enjoyment and fun. The results indicate that the users agreed on all the dimensions. The findings proved that the e-STAR application can be one of the potential solutions to the above mentioned phenomenon.